Minimum 3.5-year outcomes of operative treatment for Achilles tendon partial tears in the midportion and retrocalcaneal area - Heinz Lohrer (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Achilles tendon partial tears are not easy to diagnose and to manage. Most frequently, they are located in the midportion and insertional area. These entities result from different pathologic pathways, and different treatment strategies are applied. The outcome is rarely investigated. Methods This study includes patients who underwent surgery for partial tears in the midportion or retrocalcaneal Achilles tendon area between the years 2009 and 2015 by a single surgeon. Patients were prospectively assessed preoperatively and 3, 6, and 12 months postoperatively, using the VISA-A-G questionnaire. The final retrospective follow-up was performed after a minimum of 3.5 years postoperatively. Forty-eight Achilles tendon partial tears at the level of the retrocalcaneal bursa (impingement lesions) and 27 midportion Achilles tendon partial tears were identified. After applying rigorous exclusion criteria, 21 and 16 cases, respectively, remained for the final follow-up. Results were analysed by inferential and descriptive statistics. Results The VISA-A-G outcome scores improved significantly from preoperative to 6 months, 12 months, and final postoperative assessment. Preoperatively, the average VISA-A-G score was 42.1 (range, 18–73) for patients operated for Achilles tendon partial tears at the level of the retrocalcaneal bursa and 44.6 (range, 10–73) for the midportion Achilles tendon partial tear group, respectively. At final follow-up 88.8 (range, 15 to 100) and 96.9 (range, 71 to 100) were scored in the respective treatment groups. A repeated measures ANOVA determined that mean performance levels showed a statistically significant difference between measurements (p < 0.001). There was no systematic effect found between groups (p = 0.836). Conclusions In Achilles tendon partial tears recalcitrant to conservative treatment, operative intervention is highly successful in most cases, irrespective of the level of the injury. Results were statistically equal when comparing the midportion and retrocalcaneal Achilles tendon partial tear groups. Trial registration DRKS, DRKS00014266. Registered 06 April 2018. ‘Retrospectively registered’, https://www.drks.de/drks_web/navigate.do?navigationId=results .